Built Heritage Evaluation Manual Using Simple Test Methods - Robert J., Koestler (2021)
This manual describes simple tests for evaluating the condition of built heritage and cultural monuments. The tests were selected for their simplicity and widespread availability, especially in countries where few institutions deal with the conservation of important buildings or monuments and where laboratories capable of the necessary analyses are scarce. Most tests can be carried out without the resources of a complete conservation laboratory. Methods include microscopy, ion test strips, the Scotch Tape test, RILEM tube water absorption, water vapor transmission, and three tests that can be run sequentially: capillary water absorption coefficient, total immersion, and evaporation curves. Some of these tests aid in the examination of building materials and the characterization of salts and other condition problems, which will help to determine the appropriate methods and materials for conservation and restoration.